Circulating 25‐hydroxyvitamin D, nasopharyngeal airway metabolome, and bronchiolitis severity. Issue 5 (5th February 2018) - Hasegawa, K.; Stewart, C. J.; Celedón, J. C.; Mansbach, J. M.; Tierney, C.; Camargo, C. A.
Abstract: Low circulating 25‐hydroxyvitamin D (25OHD) levels are a risk factor for acute respiratory infection (eg, bronchiolitis) in children. However, little is known about the relation of circulating 25OHD with the many downstream functional molecules in target organs—such as the airway—and with clinical outcomes. In this prospective multicenter study of infants (age <1 year) hospitalized with bronchiolitis, we measured serum 25OHD levels and profiled the metabolome of 144 nasopharyngeal airway samples. Among 254 metabolites identified, we defined a set of 20 metabolites that are related to lower serum 25OHD and higher vitamin D‐binding protein levels. Of these metabolites, 9 metabolites were associated with a significantly higher risk of positive pressure ventilation use. These metabolites were glycerophosphocholines esterified with proinflammatory fatty acids (palmitate, arachidonate, linoleate, and stearate), sphingomyelins, alpha‐hydroxyisovalerate, 2‐hydroxybutyrate, and 3‐(4‐hydroxyphenyl)lactate (all FDR<0.05). Based on the multicenter data, vitamin D‐related airway metabolites were associated with risks of bronchiolitis severity.